OUTCOMES OF IN VITRO FERTILIZATION USING DONOR SPERM AT HANOI MEDICAL UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of in vitro fertilization using donor sperm at Hanoi Medical University Hospital.Subjects and methods: A retrospective descriptive study was conducted on 142 ovarian stimulation cycles using donor sperm for intracytoplasmic sperm injection from January 2022 to December 2023, including 81 cycles from azoospermic couples and 61 cycles from single women. Semen parameters before freezing and after thawing-processing, fertilization rates, and embryo development outcomes were analyzed using descriptive and comparative statistics.Results: Post-thawing analysis showed a significant decrease in sperm concentration and progressive motility (p < 0.001). The mean fertilization, cleavage, blastocyst formation, and good-quality blastocyst rates were 89.8%, 96.0%, 60.0%, and 23.8%, respectively. No significant differences were observed among subgroups classified by post-thaw progressive motility (p > 0.05).Conclusion: Although cryopreservation significantly reduced sperm motility and density, fertilization and embryo development outcomes remained comparable to those obtained with fresh sperm. These findings confirm the safety and effectiveness of donor sperm use in assisted reproductive technologies in Vietnam.
Keywords: Donor sperm, in vitro fertilization, ICSI.